The Troika's conditionalities during the Greek financial crisis of 2010–2014: the Washington Consensus is alive, well, and here to stay - John Marangos (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
There is a widespread perception around the world that the Washington Consensus is dead. In contrast to the world tide prior to the global financial crisis of 2008, this paper aims to demonstrate that the conditionalities inspired by the Washington Consensus and imposed by the international financial institutions are still pertinent. Using as a case study the Greek financial crisis of 2010–2014, it is verified that the Troika's austerity imposed conditionalities that neatly fit within the Washington Consensus framework. However, consistent with the neoclassical framework, the Washington Consensus recommends the reduction in taxes, whereas the Troika's austerity conditionalities entail an increase in taxes. It appears that a striking paradox is present, in that the neoclassical tax conditionality policy is sacrificed in the name of increased tax revenue. This allegedly perplexing tax policy and blatant conflict, which appears to controvert the very essence of the neoclassical ideological framework of the Washington Consensus and the IMF, will be further explored.
Keywords: O11; O52; 330; Washington Consensus; Greek financial crisis; conditionalities; Troika; IMF